إبستيمولوجيا الذكاء الإصطناعي - برتيمة,رشيدة (University of Eloued جامعة الوادي, 2024)
Abstract: This study attempts to clarify the philosophical and logical foundations of the artificial intelligence، starting with the myth that paved the way for humans to think creatively. Despite its naivety، it cannot be denied that it is something that primitive man directed as an intuitive beginning that paved the way for a scientific revolution as this myth turned into logic. With the beginnings of the expansion of human rational thinking، mathematics and logic algebra became a paving way for intellectual revolutions، which in turn contributed to the formation of scientific thought based on a rational basis. The Fourth Industrial Revolution was the most prominent scientific event because the artificial intelligence was one of its results. The artificial intelligence contributed to laying the groundwork for the philosophical foundations of its techniques in addition to identifying the most important algorithms on which it is based . الملخص: جاءت هذه الدراسة من اجل بيان الأسس الفلسفية والمنطقية للذكاء الاصطناعي، بدايتا من الأسطورة التي مهدت للإنسان الطريق للتفكير رغم سذاجتها والغباء التي كانت تحمله إلا انه لا يمكن نكران أنها شيء مبدع نتجه الإنسان البدائي، من الأسطورة انتقالا الى المنطق وبدايات التفكير العقلاني عن الإنسان، بعدها الرياضيات وجبر المنطق، الى الثورات الفكرية التي أنتجها الانسان بتفكيره العبقري التي ساهمت في تشكيل فكر علمي مبني على أساس عقلي، وكانت الثورة الصناعية الرابعة أبرزهم، حيث أنالذكاء الاصطناعي كان نتاج الثورة الصناعية الرابعة بعد ذاك انتقلنا الى الاسس الفلسفية للذكاء الاصطناعي، واهم الخوارزميات والتقنيات التي يقوم عليها الذكاء الاصطناعي .
Keywords: الابستمولوجيا; الذكاءالاصطناعي; الأسطورة; المنطق; Epistemology; Artificial intelligence; The legend; Logic